ANALYZING SERVICE QUALITY ON CUSTOMER LOYALTY IN FRESHMART BAHU MANADO - Pangemanan, David (Sam Ratulangi University, 2015)
ABSTRACT Industrial development of retail business in Indonesia was marked by the opening of the entrance to the foreign retailers as Presidential Decree of the Republic of Indonesia No. 118 of 2000 which has issued a retail business on the negative list for foreign direct investment (FDI), since that the modern retail business which is funded by local and foreign capital got increased. This study has discussed about service quality; tangibles, reliability, empathy, responsiveness, and assurance, consideration simultaneous influence the consumer loyalty. The research aims to analyze service quality on customer loyalty in modern retail market: Freshmart Bahu Manado. The main reason of this study is to reveal how service quality influence customer loyalty in Freshmart Bahu Manado. The data of this study had collected from consumers (respondents) who have experience of daily shopping activities in Freshmart Bahu Manado. Keywords: Service Quality, Responsiveness, Assurance, Empathy, Tangibles, Reliability